2012
DOI: 10.4103/1755-6783.105131
|View full text |Cite
|
Sign up to set email alerts
|

A study on mental distress among MBBS students in a Medical College, Kolkata, India

Abstract: Background:The undergraduate medical training period is a stressful period. In the recent years, due to growing competitiveness and aspiration for achievement the pressure on the students has increased manyfolds and makes the medical students more vulnerable for developing mental distress and thus contributes to poor academic performance and substance use. So an observational, cross-sectional study was conducted among the undergraduate students in a medical college to study the prevalence of mental distress am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Our observations revealed that inability to cope up with the course content was found to be significantly associated with mental distress, Similar findings have also been reported in studies conducted from Kolkata and New Delhi (2) (14) . Family history of mental illness, level of education and global satisfaction with life were other dominant risk factors associated with mental distress as observed in a study conducted among university students from New Delhi (14) .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our observations revealed that inability to cope up with the course content was found to be significantly associated with mental distress, Similar findings have also been reported in studies conducted from Kolkata and New Delhi (2) (14) . Family history of mental illness, level of education and global satisfaction with life were other dominant risk factors associated with mental distress as observed in a study conducted among university students from New Delhi (14) .…”
Section: Discussionsupporting
confidence: 91%
“…A study carried out in different regions of India reflect diverse situations depending on the use of study instruments. Similar findings were observed in the Kolkata study, where the prévalence of mental distress was found to be 14.5% among medical students (2) . A study done among medical under-graduate students in Bhubaneswar (Odisha) reported the prevalence of depression, anxiety and stress using DASS (Depression Anxiety Stress Scale) scale as 51.3%, 66.9%, and 53% respectively (11) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations